MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS 5 DENGAN MENGGUNAKAN PEMBELAJARAN KONTEKSTUAL - RUBIYATI RUBIYATI (ACADEMIA: Jurnal Inovasi Riset Akademik, 2022)
This research was carried out because of the low mathematics learning outcomes of grade 5 students at SD Negeri 1 Bategede for the 2022/2023 academic year. This is proven by the average value of daily test classes only reaching 66.05. While the minimum completeness criterion is 70.00. After the researchers conducted research through interviews and observations, the low mathematics learning outcomes were caused by many factors, including because teachers still used conventional learning methods, there were also many students who were not fluent in reading. So there are still many students who do not understand the material presented by the teacher. Of the two problems above, the researcher chose to change the way of learning, namely according to the title above "Improving Grade 5 Students' Mathematics Learning Outcomes Using Contextual Learning". Therefore the researchers conducted this classroom action research to determine the level of success in conducting learning using contextual learning models in improving the learning outcomes of grade 5 students at SD Negeri 1 Bategede in the 2022/2023 academic year. The learning process in the contextual learning model goes through 7 phases or 7 principles, namely (1) Constructing knowledge, (2) Inquiry, (3) Asking, (4) Grouping (5) Modeling, (6) Reflection, (7) Assessment. The results showed that there was an increase in the results of learning mathematics for grade 5 students, based on the observation that the average value produced in each cycle was increasing. Thus the researcher can conclude that it can improve students' mathematics learning outcomes using contextual learning models. ABSTRAKPenelitian ini dilaksanakan karena adanya hasil belajar matematika siswa kelas 5 di SD Negeri 1 Bategede tahun ajaran 2022/2023 yang rendah. Hal ini terbukti nilai rata-rata kelas ulangan harian hanya mencapai 66,05. Sementara kriteria ketuntasan minimal adalah 70,00. Setelah peneliti melakukan penelitian melalui wawancara dan observasi, rendahnya hasil belajar matematika yang rendah ternyata disebabkan oleh banyak faktor diantaranya karena guru masih menggunakan cara pembelajaran yang konvesional, banyak juga diantara siswa ada yang kurang lancar membeca. Sehingga masih banyak siswa yang tidak memahami materi yang disampaikan guru. Dari dua permasalahan diatas peneliti memilih untuk mengubah cara pembelajarannya yaitu sesuai judul diatas “Meningkatkan Hasil Belajar Matematika Siswa Kelas 5 Dengan Menggunakan Pembelajaran Kontekstual”. Oleh karena itu peneliti melakukan penelitian tindakan kelas ini guna mengetahui tingkat keberhasilan melakukan pembelajaran menggunakan model pembelajaran kontekstual dalam meningkatkan hasil belajar siswa kelas 5 di SD Negeri 1 Bategede tahun ajaran 2022/2023. Proses pembelajaran pada model pembelajaran kontekstual melalui 7 fase atau 7 prinsip yaitu (1) Mengkontruksikan pengetahuan, (2) Inkuiri, (3) Bertanya, (4) Berkelompok (5) Pemodelan, (6) Refleksi, (7) Penilaian. Hasil penelitian menunjukkan adanya peningkatan hasil belajar matematika siswa kelas 5, berdasarkan observasi nilai rata-rata yang dihasilkan pada tiap siklus yang semakin meningkat. Dengan demikian dapat peneliti simpulkan bahwa dapat meningkatkan hasil belajar matematika siswa menggunakan model pembelajaran kontekstual.